EVALUATION OF THE ANTIHYPERTENSIVE DRUGS IN PREECLAMPSIA PATIENTS TO CLINICAL OUTCOMES AT RSUD SEKARWANGI ON 2021 PERIOD - Nisa Rokhmah; Oktaviana Zunita; Alya Septiani (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Preeclampsia is a pregnancy complication with several symptoms, such as hypertension, proteinuria, and edema. Such symptoms occur in pregnant women after the gestational age reaches 20 weeks. Preeclampsia is divided into mild preeclampsia (PER) and severe preeclampsia (PEB). Antihypertensive drugs are used to lower blood pressure and proteinuria levels in patients with preeclampsia. The purpose of this study was to obtain a profile of antihypertensive drugs and monitor changes in clinical outcomes in patients with preeclampsia. This was a retrospective cross-sectional study using secondary data from the medical records of preeclampsia patients. Of the 54 patients who met the inclusion criteria with the age at which most preeclampsia was 21–35 years old, 33 (61.11%) patients and 32 (59.62%) patients had PEB. The most widely used antihypertensive drug was a combination of methyldopa and nifedipine, with 27 (50%) patients receiving combination therapy. After treatment with antihypersensitive drugs, 50 (92.60%) patients experienced a decrease in blood pressure, 45 (83.33%) patients experienced a decrease in proteinuria levels, and 45 (83.33%) patients had normal birth conditions. Antihypertensive treatment for preeclampsia patients has a relationship with a decrease in the patient’s blood pressure (p-value = 0,007), but there was no relationship with a decrease in proteinuria levels (p-value = 0,660) and condition of baby birth (p-value = 0,446). Keyword: Preeclampsia; Antihypertensive Drugs; Clinical Outcomes